Investigation of mixed micellization study of sodium dodecyl sulfate and tetradecyltrimethylammonium bromide mixtures at different compositions: Effect of electrolytes and temperatures. (28th January 2020) - Hasan, Md. Zahid; Mahbub, Shamim; Hoque, Md. Anamul; Rub, Malik Abdul; Kumar, Dileep
Abstract: Herein, we employed the conductometric measurement technique for the estimation of the interaction between two oppositely charged surfactants (anionic, sodium dodecyl sulfate [SDS] and tetradecyltrimethylammonium bromide [TTAB]) in two chloride (NaCl/NH4 Cl) salts in the range of temperatures from 298.15 to 318.15 K. The deviation of experimental critical micelle concentration ( cmc ) from the corresponding ideal values of cmc ( cmc id ), the values of interaction parameters ( β ), and activity coefficients ( f 1 and f 2 ) of the components reveal the existence of the interaction amongst the investigated components. The attained cmc values for SDS/SDS + TTAB decline with the rise of temperature in H2 O/electrolytes medium. The reduction of cmc in the presence of electrolytes reveals the facilitated micellization in the electrolyte medium. The assessed values of the micellar mole fraction of TTAB ( X 1 ) obtained from theoretical models signify the significant contribution of TTAB in SDS + TTAB mixed micellization. The estimated negative values of free energy ( Δ G m o ) and excess free energy ( ΔG ex ) of micellization reveal that micellization is spontaneous and mixed micelles are extra stable than distinct micelle, respectively. The enthalpy ( Δ H m o ) and entropy ( Δ S m o ) in addition transfer energies of micellization were also evaluated and explained thoroughly. Abstract : We employed the conductometric measurement for the interaction between SDS and TTAB in NaCl/NH4 Cl from 298.15 K to 318.15 K. The deviation cmc from the corresponding ideal values of cmc ( cmc id ) and the values of interaction parameters ( β ) of the components reveal the existence of the interaction amongst components. The enthalpy ( Δ H m o ) and entropy ( Δ S m o ) in addition transfer energies of micellization were also evaluated.